CRISES AND REFORM: TWO SIDES OF THE SAME COIN? (Hekima Review, 2023)
The discourse on the reforms has increasingly become multi-disciplinary. In many cases, conservative versus liberal opinions mar the process of reforms. Yet, engaging in reforms simply implies the readiness for perspectival shifts, embracing new changes, and rebranding good old habits. Reforms imply a thoughtful and deliberate back-and-forth shift in responding to existential realities. Pedagogues, for instance, perceive 'reform' as a learning model, a consequence of problem-seeking-solution learning. This approach prioritizes a question-answer, problem-solving engagement where questions or problems become opportunities for advancement.